PHYSICAL FITNESS TESTS FOR SKI JUMPERS - Fendel, T.V.; Zubkov, D.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze benefits of a physical fitness test model for the ski jumping sport versus the valid Federal Sports Training Standards for training progress stages. Methods and structure of the study. Benefits of the new physical fitness test model were tested on a sample representing two federal regions and three sports organizations that provide modern ski jumping training services including: (1)"Stork" Olympic Reserve Sports School (ORSS), Nizhny Tagil city; (2) "Start" ORSS, Perm city; and (3) “Flying skier" ORSS, Perm city. The ski jumpers sample (n= 269, 157 boys and 112 girls) was grouped by the training/ progress stages as follows: Beginner group: 79 boys and 60 girls; Specializing group: 55 boys and 33 girls, Excellence group: 16 boys and 13 girls; and Elite group: 7 boys and 6 girls. The group test data were benchmarked versus the Federal Sports Training Standards for the relevant ski jumping progress groups. Results and conclusion. The group test data and analysis showed that the valid Federal Sports Training Standards being irrelevant, uninformative and inefficient for the progress tests in the modern ski jumping sport training and competitive fitness rating systems. The physical fitness tests in the Federal Sports Training Standards need to be revised to provide a sound basis for competitive progress analysis in the ski jumping sport groups. The Federal Sports Training Standards tests need to be also harmonized with the valid GTO Test system to ensure the group test standards being practical and efficient for the progress tests at every training stage.